Finding Nemo: A Psychoanalytic Study of Marlin and Nemo - Lee, Gloria Hope; Manina, Miralda Ruth; Manurung, Markley Nathanael Sumandoro; Miarso, John Prince (Jurnal Pendidikan Makarios, 2026)
This study looks at psychological themes such as trauma, independence, and overprotectiveness in parents that are often rooted to past trauma and fear. The movie Finding Nemo (2003) strongly portrays them through Marlin's unresolved grief of losing his loved one and past trauma. Examining how Marlin's trauma influences his overprotective behaviour towards Nemo, how Nemo’s pursuit of independence represents a child’s desire for freedom from parental control, and how the opposing forces of freedom and oppression reflect the Freudian theory, “The Unconscious” (1957). Using Freud’s concepts of the unconscious, repression, melancholia, and repetition compulsion combined with selected scenes, dialogues, and cinematography from the movie to analyze Marlin’s behavior. As the results: 1) Marlin's overprotective character stems from his past trauma of losing his loved ones, leading him to constantly monitor Nemo and undermine his confidence. 2) Nemo's defiance of his father's warnings is an expression of a child's drive for independence and autonomy from parental supervision. 3) This quest for freedom is intensified by Nemo's need to validate his own abilities, particularly after feeling undermined by Marlin's overprotective and restrictive language. The film effectively demonstrates how Marlin's unresolved trauma and guilt shape his parenting often manifesting as anger and prevent him from allowing Nemo the space to grow. The study concludes that by analyzing Finding Nemo demonstrates how trauma can drive unconscious decision making and how childhood independence grows when parents confront and overcome their own trauma. It offers insights into the impact of trauma on parenting, the development of independence, and the unconscious forces that shape relationships and personal growth.